Implementasi Kebijakan Penataan Kawasan Pesisir Dalam Mewujudkan Pembangunan Berbasis Waterfront City Di Kota Bau Bau Provinsi Sulawesi Tenggara - Takwim Takwim (Jayapangus Press, 2020)
Policy Implementation Coastal Area Based Development In Realising Waterfront City in Kota Baubau. The Impementasi Coastal Area Based Development In Realising Waterfront City can Seen From The beisis Policy Interests The affected Posted policy, Operate The benefits generated will, desired degree of change That will, Position policymakers, program implementers Who, What deployed Resources and Context Implementation lying between Power, interest and Development The strategy of the actors involved, Characteristics Institutions And Ruler, Compliance And grasp of policy implementers. for derive the implementation and the factors affecting the Coastal Area Based Development In Realising Waterfront City in Kota Baubau.